Needle Revision of Failed Drainage Blebs with Mitomycin-C - Israr A. Bhutto, Dilshad A. Laghari, P. S. Mahar, A. Sami Memon (Pakistan Journal of Ophthalmology, 2018)
Purpose: To assess the outcome of needle revision of failed drainage blebs with regard to decrease in Intraocular pressure (IOP) of < 20 mmHg over mean follow up of 1 year and to observe the complication associated with the procedure. Material and Methods: This non-comparative, interventional case series of 46 eyes (46 patients) with IOP of > 25 mmHg after trabeculectomy were subjected to needle revision with mitomycin-C (MMC) from January 2007 to December 2010. Thirty four patients were male and 12 were female with age ranging from 47 to 72 years. Results: Twenty six patients (26 eyes) out of 46 patients (46 eyes) showed improvement in IOP of < 20 mmHg, achieving success at 57%. The preoperative mean IOP of our patients was 26.7 ± 6 mmHg (95% Confidence Interval 25.16 – 28.23), while post-operative mean IOP was 13.5 ± 4 mmHg (95% Confidence Interval 12.47 – 14.5) at the mean follow up of 1 year. Transient hyphema was noticed in 1 patient (2.17%) and 2 patients (4.34%) went into hypotony with IOP of < 6 mmHg. All these eyes resolved spontaneously with no additional treatment. Conclusion: Needle revision of drainage blebs with MMC revived failed filtration procedure in 57% of our patients at the mean follow up of 1 year with minimal complications.